Computer simulation of a new type heat engine operation - Brzeski, Lech; Kazimierski, Zbyszko (Computer Assisted Methods in Engineering and Science, 1995)
A new type of the externally heated engine is the subject of the present paper. Air can be used as a working medium of the engine. Heat delivered to the working air may come from a combustion chamber or another heat generator of an arbitrary type. The engine construction and the thermodynamic cycle performed by the engine are original ones. The engine operation has been investigated basing on the presented computer simulation. As a result, the time-dependent pressures and temperatures in each part of the engine have been determined. The engine power and efficiency have also been calculated. When the lowest basic pressure of the engine cycle is equal to 1 MPa, the power of 30 kW per 1 liter of the cylinder volume and the efficiency 0.38 at 1500 rev/min can be achieved. The main aim of this paper is to present a numerical investigation of the engine operation for higher values of the basic cycle pressures. It has been shown that for the pressure equal to 3 MPa, the power of about 100 kW per 1 liter and the efficiency 0.40 at 1500 rev/min can be theoretically obtained. The mechanical losses of the engine are not taken into account during the power and efficiency calculations.